CONODONT BIOSTRATIGRAPHY AND FAUNAL ASSEMBLAGES IN RADIOLARIAN RIBBON-BANDED CHERTS OF THE BURUBAITAL FORMATION, WEST BALKHASH REGION, KAZAKHSTAN - Tolmacheva T.; Holmer L.; Gogin I.; Popov L. (My University, 2004)
Biostratigraphical study of the early to mid-Ordovician conodont fauna from ribbon-banded radiolarian cherts of the middle Burubaital Formation in Central Kazakhstan reveals an almost complete succession of conodont biozones from the late Tremadocian to the early Darriwilian. During this interval, biosiliceous sediments were deposited in basinal environments, inhabited by lingulate brachiopods, sponges, pterobranchs and caryocaridids in conditions of high fertility and primary productivity of surface water. The community structure of taxonomically diverse conodont assemblages typifying open oceanic environments is not significantly different from that of epicratonic basins of the North Atlantic conodont province. The regional increase of oxygenated bottom waters at the base of the Oepikodusevae Biozone is possibly related to considerable changes in palaeo-oceanographical circulation patterns. The finds of three natural clusters of Prioniodusoepiki (McTavish) enable us to propose an emended diagnosis of this species.
Keywords: Paleozoic::Ordovician; Палеозой::Ордовикская